2008
DOI: 10.1002/srin.200806210
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and Experimental Investigations of Steel Mixing Time in a 130-t Ladle

Abstract: This paper presents the experimental determination of variations in the chemical composition of a steel bath after introducing an alloy addition, and a numerical simulation corresponding to the conditions in an industrial ladle furnace. The numerical model and experimental studies aimed to determine the mixing time necessary for achieving the assumed degree of chemical homogenisation under the conditions of operation of the ladle furnace. In addition, through the numerical studies, the metal bath mixing time f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 30 publications
(31 reference statements)
0
22
0
Order By: Relevance
“…They reported a value of 7-8 minutes, independently of the ladle size. In contrast to these values, Warzecha et al 16) and Aoki et al 17) have reported mixing times in the range from 1.5-3 minutes for ladles of 110-140 tonnes, using gas flow rates in the order of 10 Nm 3 /hr. The large differences reported for mixing times in industrial size ladles can be attributed to different porous plugs configurations (i.e., number and location) as well as gas flow rate, however our current numerical predictions suggest that mixing times in industrial size ladles is at least one order of magnitude higher in comparison with water models.…”
Section: δT T T Z Z Zmentioning
confidence: 88%
See 1 more Smart Citation
“…They reported a value of 7-8 minutes, independently of the ladle size. In contrast to these values, Warzecha et al 16) and Aoki et al 17) have reported mixing times in the range from 1.5-3 minutes for ladles of 110-140 tonnes, using gas flow rates in the order of 10 Nm 3 /hr. The large differences reported for mixing times in industrial size ladles can be attributed to different porous plugs configurations (i.e., number and location) as well as gas flow rate, however our current numerical predictions suggest that mixing times in industrial size ladles is at least one order of magnitude higher in comparison with water models.…”
Section: δT T T Z Z Zmentioning
confidence: 88%
“…Only few investigations have reported mixing time for industrial size ladles. [13][14][15][16][17] Abel et al 13) compared water modelling results and industrial size ladles, reporting mixing times one order of magnitude higher for industrial size ladles. In the experimental work of Schurmann et al reported by Mietz et al 14) a mixing time of approximately 12 minutes is reported for an industrial ladle of 120 tonnes.…”
Section: δT T T Z Z Zmentioning
confidence: 99%
“…Liu et al (9) measured slag eye area in a water model for different gas flow rates, slag layer thickness and porous plug locations. Several numerical simulation models [10][11][12][13] have been proposed for investigating the fluid flow and mixing phenomena in gas stirred ladles. Mazumdar et al (14) made an extensive review of physical modelling, combined physical and mathematical modelling and mathematical modelling studies.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the convenient solution is to carry out research with the use of water models and computational simulation (applied commonly in metallurgy of steel and non-ferrous metals) [6][7][8][9][10][11][12][13]. Fig.…”
Section: Introductionmentioning
confidence: 99%